Politik Ekonomi As dan Kondisi Perdagangan Internasional Pasca Pandemi Global - Mirahandani M; Egianinta Br Ginting; Rut Madia Harefa; Vincetia Avetriwianda Sinabutar; Widya Puspita; Hafiza Adlina (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Lacking supportive public policies in the past, many American workers and communities have borne the costs of shifting production around the world but have yet to fully reap the benefits, contributing to widening inequality. Addressing this deficiency requires policies that expand the gains from trade while leveling the international economic playing field by combating unfair trade practices and implementing a more equitable global tax system. Implementing such policy changes in a way that reduces uncertainty and engages with the United States' trading and commercial partners can ensure that American consumers, workers, businesses, and investors benefit from global trade. This paper aims to place America's economic experience during the pandemic in a global context by comparing it to our largest trading partners: the euro area, the UK, China, Canada and Mexico. The next section examines how international trade has recovered from the sharp downturn caused by the pandemic, examining the causes of the widening US trade deficit and the impact of international supply chain bottlenecks on traded inputs such as auto parts and capital goods. The final section examines how the Biden-Harris Administration reoriented US international economic policy to reduce, rather than exacerbate, economic inequality and to equalize the international economic standing.